Modeling of a solar water heating system for a private hospital in Sana’a, Yemen using TRNSYS: دراسة استخدام الطاقة الشمسية لإنتاج المياه الساخنة لمستشفى خاص في صنعاء باستخدام برنامج المحاكاة TRNSYS - Abduljalil Ali Al-Abidi, Abdulkarem A. Odhah (Journal of engineering sciences and information technology, 2021)
The objective of the present work is to simulate and analysis the performance of a proposed solar water heating system for a 160-bed capacity private hospital in Sana’a City-Yemen. The systems consist of solar collectors, hot water circulation pump, a storage tank with an electrical heater, and identical auxiliary components. The simulation and the thermal performance analysis have been done using TRNSYS software. In addition, a comparison between the performance of evacuated tubes collectors and flat plate collectors was done to justify the selection of ETC for the designed. The thermal performance analysis shows that the evacuated tubes collectors have an annual contribution of 87.73 MWh with an annual average solar fraction of 63 percent and annual average installation efficiency of 68 percent.